Methyl 2-(4-chloro-3,5-dinitrobenzamido)acetate - Wu, Xiang-Xiang; Wu, Xue-Fen; Hou, Yi-Min; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
The title molecule, C10H8ClN3O7, is twisted with the dihedral angle between the amide and benzene ring being 38.75 (11)degrees. The C-N-C-C torsion angle between the amide and acetyl groups is -150.1 (2)degrees. Finally, each nitro group is twisted out of the plane of the benzene ring to which it is connected [O-N-C-C torsion angles = 34.0 (3) and -64.5 (3)degrees]. Linear supramolecular chains along [010] and mediated by N-H center dot center dot center dot O hydrogen bonds between successive amide groups dominate the crystal packing. The chains are consolidated into the three-dimensional structure by C-H center dot center dot center dot O contacts.